BIOPROSPECÇÃO DE FUNGOS ISOLADOS DE REMANESCENTES DE FLORESTA OMBRÓFILA MISTA PRODUTORES DE LIPASES: POTENCIAL LIPOLÍTICO DE Trichoderma sp. - GUIMARÃES, MICHAEL WILIAN (2016)
The soil from Araucaria forest had been the focus of few studies about its microbial diversity. The soil is a habitat that exhibits a large microbial diversity. Thus, it can be explored as a source of microorganisms that produce enzymes of industrial interest. Among of variousenzymes existent, the lipases (triacylglycerol-acid-hydrolases E.C.3.1.1.3) are extensively used, due to the wide range of reactions that they catalyze, as the total or partial hydrolysis of triacylglycerols (TAG), reactions of esterification, transesterification and inter-esterification of lipids. Therefore, the present study aimed to isolate different fungal strains from fragments of Araucaria Forest and evaluate the potential of lipase production by the fungi isolated. From the selection of the best producer strain, the Design Plackett-Burman was used, in order to select the variables that affect this process. After, the Central Composite Rotatable Design (CCRD) applicable to Response Surface Methodology (RSM) was employed, in order to establish the best conditions for the lipase production, using the castor bean waste as substrate. Finally, the enzyme produced under optimum conditions were biochemically characterized. The fungal isolation was conducted using the dilution series technique, allowing the achievement of 65 fungal strains. The lipase production capacity was verified in 17 of studied strains, in which a Trichoderma strain was the best producer. Tween 80, CaCl2, NH4Cl and yeast extract were selected as the variables that affect the lipase production process by Trichoderma sp. For this reason, these same variables were considered in DCCR. Under optimized conditions, the levels of lipases reached 64 U mL-1. Through the biochemical characterization, it was possible stablished that Trichoderma sp. lipases showed optimal activity in neutral pH, at 30 °C. In relation to the effect of various ions and substances on the lipase activity, 0.2 mM Na+2 activated these enzymes. In addition, an activator effect was verified in the presence of Triton X-100 surfactant. Among distinct organics solvents evaluated, only 1% toluene presented an activator effect on the produced enzymes. The results obtained in this study reveal the potential use of the castor bean waste as substrate for the lipase production. The employment of this waste on microbial enzymes production is very interesting, since economic and environmental benefits could be obtained from its uses. In addition, the screening studies presented here offer news perspectives, in order to promote the appreciation as well the rational exploration of Araucaria Forest fragments, priority areas for the Brazilian biodiversity conservation.